Rapid and Laboratory SARS-CoV-2 Antibody Testing in High-Risk Hospital Associated Cohorts of Unknown COVID-19 Exposure, a Validation and Epidemiological Study After the First Wave of the Pandemic - O'Kelly, Brendan; McLaughlin, Ronan; O'Doherty, Roseann; Carroll, Hailey; Murray, Roisin; Dilworth, Rachel; Corkery, Laura; Cotter, Aoife G.; McGinty, Tara; Muldoon, Eavan G.; Cullen, Walter; Avramovic, Gordana; et al. (Frontiers in Medicine, 2021)
Objective: We aimed to use SARS-CoV-2 antibody tests to assess the asymptomatic seroprevalence of individuals in high-risk hospital cohorts who's previous COVID-19 exposure is unknown; staff, and patients requiring haemodialysis or chemotherapy after the first wave. Methods: In a single Center, study participants had five SARS-CoV-2 antibody tests done simultaneously; one rapid diagnostic test (RDT) (Superbio Colloidal Gold IgM/IgG), and four laboratory tests (Roche Elecsys® Anti-SARS-CoV-2 IgG [RE], Abbott Architect i2000SR IgG [AAr], Abbott Alinity IgG [AAl], and Abbott Architect IgM CMIA). To determine seroprevalence, only positive test results on laboratory assay were considered true positives. Results: There were 157 participants, of whom 103 (65.6%) were female with a median age of 50 years (range 19–90). The IgG component of the RDT showed a high number of false positives (n = 18), was inferior to the laboratory assays (p < 0.001 RDT vs. AAl/AAr, p < 0.001 RDT vs. RE), and had reduced specificity (85.5% vs. AAl/AAr, 87.2% vs. RE). Sero-concordance was 97.5% between IgG laboratory assays (RE vs. AAl/AAr). Specificity of the IgM component of the RDT compared to Abbott IgM CMIA was 95.4%. Ten participants had positivity in at least one laboratory assay, seven (9.9%) of which were seen in HCWs. Two (4.1%) hematology/oncology (H/O) patients and a single (2.7%) haemodialysis (HD) were asymptomatically seropositive. Asymptomatic seroprevalence of HCWs compared to patients was not significant (p = 0.105). Conclusion: HCWs (9.9%) had higher, although non-significant asymptomatic seroprevalence of SARS-CoV-2 antibodies compared to high-risk patients (H/O 4.1%, HD 2.7%). An IgM/IgG rapid diagnostic test was inferior to laboratory assays. Sero-concordance of 97.5% was found between IgG laboratory assays, RE vs. AAl/AAr.